2011
DOI: 10.5713/ajas.2011.10388
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Triticale Dried Distillers Grains with Solubles on Ruminal Bacterial Populations as Revealed by Real Time Polymerase Chain Reaction

Abstract: Real time PCR was used in this study to determine the effect of triticale dried distillers grains with solubles (TDDGS) as a replacement for grain or barley silage in finishing diets on the presence of six classical ruminal bacterial species (Succinivibrio dextrinosolvens, Selenomonas ruminantium, Streptococcus bovis, Megasphaera elsdenii, Prevotella ruminicola and Fibrobacter succinogenes) within the rumen contents of feedlot cattle. This study was divided into a step-wise adaptation experiment (112 days) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The DDGS is the soluble and solid residues by-produced in ethanol fermentation process using grain sources ( Liu, 2011 ), and has been used as an animal feed ingredient ( Wu et al, 2011 ). There has been an interest in the use of DDGS for industrial enzyme production since it is inexpensive relative to high protein and carbohydrate contents.…”
Section: Resultsmentioning
confidence: 99%
“…The DDGS is the soluble and solid residues by-produced in ethanol fermentation process using grain sources ( Liu, 2011 ), and has been used as an animal feed ingredient ( Wu et al, 2011 ). There has been an interest in the use of DDGS for industrial enzyme production since it is inexpensive relative to high protein and carbohydrate contents.…”
Section: Resultsmentioning
confidence: 99%
“…Fibrobacter succinogenes tended to be greater in lambs fed SH than in lambs fed BP, and it was greater in lambs fed the high starch than in lambs fed the low starch level. Previous studies showed that replacing barley silage with dried distiller triticale grains in feedlot cattle increased the amount of F. succinogenes ( Wu et al, 2011 ). These findings agreed with the understanding that F. succinogenes abundance is related to the type of forage diet ( Tajima et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…at a ruminal pH below than 5.4, causing excess lactate accumulation and cow death from acidosis. Lactate-utilizing bacteria, such as Megasphaera elsdenii and S. ruminantium S137, begin to proliferate in response to lactic acid accumulation and remove it by converting it to volatile fatty acids (VFAs) that can be absorbed in the rumen [28,32]. Furthermore, the inoculation or supplementation of rumen bacteria in rearing cattle may increase performance, such as feed intake, feed conversion and body weight [11,15].…”
Section: Introductionmentioning
confidence: 99%